Ownership Structure and Agency Cost Case Study on Manufacturing Company in Indonesia Stock Exchange - Sutrisno; Ulfah, Tiara Annisa (Asian Journal of Empirical Research, 2021)
The frequent occurrence of conflicts of interest between shareholders and management, causing agency problems. One way to overcome this issue is to include managerial ownership (Jensen & Meckling, 1976). The purpose of this research is to examine the effect of ownership structure on agency costs. The structure of ownership consists of managerial ownership that measured by the portion of share owned by managemnt, institutional ownership measured by the portion of share owned by financial instsution, government ownership measured by the portion of share owned by government, and foreign ownership that measured by the portion of share owned by foreign invetors. The population in this research is manufacturers listed on the Indonesia Stock Exchange (IDX) with a sample of 102 companies taken by purposive sampling method. To test the hypothesis, the research uses multiple regression analysis with a significance level of 0.05. The results show that managerial ownership and institutional ownership have no significant effect on agency costs. Likewise, government ownership and foreign ownership also have no significant effect on agency costs. This indicate that in manufacturing companies in Indonesia ownership structure cannot be used to controlagency cost.